Phenomenological sedimentation model for an industrial circular settling tank - Gosar, Leon (Strojniški vestnik, 2009)
The paper presents a study of the influence of integral parameters of an industrial settling tank on the process of sedimentation. An organic water suspension was used in the experiment where the impact of the suspension age on sedimentation was determined experimentally and by computer-aided visualization. Measurements of the inlet- and outlet suspension concentration, the difference in the level of suspension between the reservoir and settling tank as well as the suspension volume flow rate were carried out on a newly developed continuous sedimentation tank. The results of the measurements served as the basis for a phenomenological multi-regression model that was developed to determine the functional dependence of the ratio between inlet- and outlet suspension concentration on the independent parameters of the process. According to the obtained results of the model, the most influential parameters of the sedimentation process are the inlet concentration and the mass flow of the suspension.
Keywords: čiščenje odpadnih voda; čistilne naprave; usedalnik; sedimentacija; vizualizacija